THE EFFECT OF MULTISENSORY DENTAL EDUCATION METHODS TO INCREASING BRUSHING TEETHS’ SKILL IN BLIND CHILDREN AT JAMBI CITY - Mira Sri Gumilar; Rusmiati Rusmiati; Slamet Riyadi (Poltekkes Kemenkes Jambi, 2020)
Background: Children with visual impairment have poor oral health. The unhealthy condition of the oral cavity of blind children is caused by several factors, unsupervised tooth-brushing activities, improper ways of brushing teeth, motor skills, and mentoring assistance that are still ignored. A study shows that poor oral and dental health status in blind children is caused by a lack of understanding and mastery of dental and oral hygiene practice techniques. For this reason, promotive service efforts are needed to improve the oral and dental hygiene of children with visual impairments. One of the promotive services provided is the right way to brush teeth. Promotive service efforts for children with visual impairment can be done by multisensory education methods. Method: The design of this study was a quasi-experimental study using the pre-test and post-test design with control group methods. Result: This study showed an increase in the average score of tooth brushing skills in the control group and treatment group. The results of the bivariate analysis showed that there were differences in tooth brushing skills before counseling and after counseling. Conclusion: the results of the study indicate that there is an influence of the multisensory method of dental education in improving toothbrushing skills.